Tathbiq Al-Thoriqoh Al-Qiyasiyah Li Ta’lim Al-Nahwu Bi Istikhdami Kitab Matan Al-Ajrumiyyah Fi Al-Fashli Al-Tsani Fi Al-Madrasah al-Islamiyyah al-Salfiyyah “Riyadhoh Al-Uqul” Pacul Gowang Jombang (April & October, 2024)
This study aims to determine the application of the qiyasiyah method in learning nahwu using the matan al-jurumiyah book at madrasah islamiyah as salafiyah riyadhotul uqul. The type of research used is qualitative research, so in achieving this goal the researcher uses 3 data collection methods, namely: observation method, interview method, and documentary method. Deductive teaching method (qiyasiyah) is one of the methods used in teaching nahwu material. In the application of this method the teacher explains first some of the nahwu rules and then continues by providing example sentences that support students' understanding of the examples to be studied, then the teacher gives examples and asks students to work on practice questions and closes by providing material conclusions. So this research is intended to find out the application of the qiyasiyah method in nahwu learning using the matan al-jurumiyah book and find out what the advantages and disadvantages of applying the qiyasiyah method in nahwu learning using the matan al-jurumiyah book are. From the analysis carried out, the researchers found several points and conclusions, namely as follows: 1) the deductive method (qiyasiyah) is the method that is more often used in nahwu learning using the matan al-jurumiyah book for grade 2 ibtida' in madrasah Islamiyah as salfiyah riyadhotul uqul than other methods, this is due to its compatibility with the madrasa curriculum. The teaching steps applied are a) introduction (muqoddimah) b) explaining the rules of Nahwu c) understanding and memorizing the rules of Nahwu d) giving examples or texts related to the rules. e) doing practice questions. f) lesson conclusions. 2) the advantages and disadvantages of applying the qiyasiyah method in learning nahwu using the book of matan al-jurumiyah class 2 ibtida' at madrasah islamiyah as salafiyah riyadhotul uqul.